Inhalation of the reactive aldehyde acrolein promotes antigen sensitization to ovalbumin and enhances neutrophilic inflammation. (3rd March 2016) - O'Brien, Edmund; Spiess, Page C.; Habibovic, Aida; Hristova, Milena; Bauer, Robert A.; Randall, Matthew J.; Poynter, Matthew E.; van der Vliet, Albert
Abstract: Acrolein (ACR), an α, β -unsaturated aldehyde and a major component of tobacco smoke, is a highly reactive electrophilic respiratory irritant implicated in asthma pathogenesis and severity. However, few studies have directly investigated the influence of ACR exposure on allergen sensitization and pulmonary inflammation. The present study was designed to examine the impact of ACR inhalation on allergic sensitization to the inhaled antigen ovalbumin (OVA), as well as pulmonary inflammation during subsequent OVA challenge. Adult male C57BL/6 mice were exposed to inhaled OVA (1%, 30 min/day, 4 days/week) and/or ACR (5 ppm, 4 h/day, 4 days/week) over 2 weeks and subsequently challenged with aerosolized OVA (1%, 30 min/day) over three consecutive days. Serum anti-OVA IgG1 levels were increased significantly in animals exposed to both OVA and ACR, compared to animals exposed to either OVA or ACR alone. In addition, differential cell counts and histological analysis revealed an increase in BAL neutrophils in animals exposed to both OVA and ACR. However, exposure to both OVA and ACR did not influence mRNA expression of the cytokines il5, il10, il13 or tnfa, but significantly increased mRNA expression of ccl20 . Moreover, ACR exposure enhanced lung mRNA levels of il17f and tgfb1, suggesting development of enhanced inhalation tolerance to OVA. Overall, the findings indicate that ACR inhalation can promote airway-mediated sensitization to otherwise innocuous inhaled antigens, such as OVA, but also enhances immune tolerance, thereby favoring neutrophilic airway inflammation.